Advertisements
Advertisements
Question
Solve the following quadratic equation:
\[x^2 - \left( 3\sqrt{2} + 2i \right) x + 6\sqrt{2i} = 0\]
Solution
\[ x^2 - \left( 3\sqrt{2} + 2i \right) x + 6\sqrt{2}i = 0\]
\[ \Rightarrow x^2 - 3\sqrt{2} x - 2i x + 6\sqrt{2}i = 0\]
\[ \Rightarrow x\left( x - 3\sqrt{2} \right) - 2i\left( x - 3\sqrt{2} \right) = 0\]
\[ \Rightarrow \left( x - 3\sqrt{2} \right)\left( x - 2i \right) = 0\]
\[ \Rightarrow \left( x - 3\sqrt{2} \right) = 0 \text { or } \left( x - 2i \right) = 0\]
\[ \Rightarrow x = 3\sqrt{2}, 2i\]
\[\text { So, the roots of the given quadratic equation are 3 }\sqrt{2} \text { and } 2i . \]
APPEARS IN
RELATED QUESTIONS
Solve the equation 27x2 – 10x + 1 = 0
x2 + 1 = 0
9x2 + 4 = 0
x2 + 2x + 5 = 0
4x2 − 12x + 25 = 0
\[x^2 - 4x + 7 = 0\]
\[x^2 + 2x + 5 = 0\]
\[21 x^2 + 9x + 1 = 0\]
\[x^2 - x + 1 = 0\]
\[21 x^2 - 28x + 10 = 0\]
\[8 x^2 - 9x + 3 = 0\]
\[13 x^2 + 7x + 1 = 0\]
\[\sqrt{3} x^2 - \sqrt{2}x + 3\sqrt{3} = 0\]
\[x^2 + \frac{x}{\sqrt{2}} + 1 = 0\]
\[- x^2 + x - 2 = 0\]
Solving the following quadratic equation by factorization method:
\[x^2 + \left( 1 - 2i \right) x - 2i = 0\]
Solve the following quadratic equation:
\[x^2 - \left( 2 + i \right) x - \left( 1 - 7i \right) = 0\]
Solve the following quadratic equation:
\[i x^2 - 4 x - 4i = 0\]
Solve the following quadratic equation:
\[x^2 + 4ix - 4 = 0\]
If a and b are roots of the equation \[x^2 - px + q = 0\], than write the value of \[\frac{1}{a} + \frac{1}{b}\].
Write roots of the equation \[(a - b) x^2 + (b - c)x + (c - a) = 0\] .
Write the number of quadratic equations, with real roots, which do not change by squaring their roots.
If α, β are roots of the equation \[x^2 - a(x + 1) - c = 0\] then write the value of (1 + α) (1 + β).
The complete set of values of k, for which the quadratic equation \[x^2 - kx + k + 2 = 0\] has equal roots, consists of
If a, b are the roots of the equation \[x^2 + x + 1 = 0, \text { then } a^2 + b^2 =\]
The values of x satisfying log3 \[( x^2 + 4x + 12) = 2\] are
If α, β are the roots of the equation \[x^2 + px + 1 = 0; \gamma, \delta\] the roots of the equation \[x^2 + qx + 1 = 0, \text { then } (\alpha - \gamma)(\alpha + \delta)(\beta - \gamma)(\beta + \delta) =\]
If the roots of \[x^2 - bx + c = 0\] are two consecutive integers, then b2 − 4 c is
If the equations \[x^2 + 2x + 3\lambda = 0 \text { and } 2 x^2 + 3x + 5\lambda = 0\] have a non-zero common roots, then λ =
The value of p and q (p ≠ 0, q ≠ 0) for which p, q are the roots of the equation \[x^2 + px + q = 0\] are
The number of roots of the equation \[\frac{(x + 2)(x - 5)}{(x - 3)(x + 6)} = \frac{x - 2}{x + 4}\] is
If α, β are the roots of the equation \[x^2 + px + q = 0 \text { then } - \frac{1}{\alpha} + \frac{1}{\beta}\] are the roots of the equation
The least value of k which makes the roots of the equation \[x^2 + 5x + k = 0\] imaginary is
Find the value of a such that the sum of the squares of the roots of the equation x2 – (a – 2)x – (a + 1) = 0 is least.
If `|(z - 2)/(z + 2)| = pi/6`, then the locus of z is ______.